Pendampingan Dalam Literasi Media Digital bagi Orang tua dan Guru di Desa Plosowahyu Kec. Lamongan Kab. Lamongan - Yayuk Chayatun Machsunah; Hadi Suryanto (Community: Jurnal Pengabdian Kepada Masyarakat, 2021)
For now, digital media is widely accessed by people from all walks of life and ages. But many of them do not use it properly, for that assistance in the use of digital media, especially for mothers and teachers which is a milestone in learning in families and schools needs to be done so that mothers and teachers have the ability to access digital media so that they can provide assistance to their children and students. The objectives of community service activities carried out by PGRI Adi Buana University Surabaya include: 1) Providing education and also conducting socialization to mothers and teachers about the characteristics of digital media that are widely accessed by children today, 2) Providing knowledge about the impact of use of digital media, 3) Provide encouragement and encouragement to mothers and teachers to provide assistance to children and students in regulating the use of digital media. The method used is socialization, discussion and also mentoring. The targets of this activity are mothers and teachers in Plosowahyu Village, Lamongan District, Lamongan Regency. The program was carried out in October and November 2021. The results of this activity: 1) mothers and teachers increasingly understand the characteristics of digital media, 2) mothers and teachers understand more about the impact of using digital media on the behavior and psychological development of children. children, 3) mothers and teachers are increasingly effective in assisting children and students in regulating the use of digital media.